A Decoupling Module Based on a Geometrical-Balance Mechanism for Mitigating Cable Length Variation in Cable-Driven Applications - Van Pho Nguyen; Sunil Bohra Dhyan; Wai Tuck Chow (Machines)
Cable-driven mechanisms are increasingly popular in applications requiring low-inertia operation. However, issues like cable loosening, which leads to reduced durability and stability with long-term use, have not been fully addressed in previous studies. This paper presents a novel design for a decoupling mechanism based on the geometrical-balance principle. The mechanism incorporates three pulleys—main, minor, and guiding—mounted on a parallelogram structure. The cable passes over these pulleys and an elbow pulley with constant tension, maintained through a balance between the pulleys’ radii and the cable’s thickness and radius. A theoretical model was developed to estimate deviations in the cable tension within this design, considering general geometric parameters and friction coefficients. In the experimental setup, the main pulley had a radius of 15 mm, while the minor, guiding, and elbow pulleys had radii of 7 mm, and a 1 mm radius Dyneema cable was used. The results demonstrated that the decoupling mechanism maintained a consistent cable length and tension with minimal deviation as the two links rotated from small to large angles. Furthermore, a strong correlation between the theoretical estimates and experimental validation confirmed that the cable tension remained stable at both ends when the decoupling mechanism was integrated into the original system. This research improves the stability and durability of cable-driven mechanisms while offering a compact, accurate solution adaptable to a wide range of applications, including robotics, machinery, and other devices.